Obesity-related Cancers: The Coming Epidemic - Venniyoor, Ajit (Indian Journal of Medical and Paediatric Oncology, 2020)
The world is in the grip of an obesity pandemic, with tripling of obesity rates since 1975; it is predicted that one-third of people on Earth will be obese by 2025. The health consequences of obesity are primarily thought to be related to cardiometabolic disorders such as diabetes and cardiovascular diseases. It is less well appreciated that obesity has been related to at least 13 different cancers and in future, (with increasing control over tobacco misuse and infections), obesity will be the main cause of cancers. While this is an area of active research, there are large gaps in the definition of what is an obesity related cancer (JRC) and more importantly, what are the underlying mechanisms. To an extent, this is due to the controversy on what constitutes “unhealthy obesity” which is further related to the causes of obesity. This narrative review examines the causes and measurement of obesity, the types of obesity-related cancers and possible mechanisms. The information has wide implications ranging from prevention, screening, prognosis and therapeutic strategies. Obesity related cancers should be an area of high-priority research. Oncologists can contribute by spreading awareness and instituting management measures for individual patients in their care.
Keywords: Carbohydrate-insulin model; gut microbiome; hyperinsulinemia; obesity; obesity-related cancers; sarcopenic obesity